Der Erste Weltkrieg. Deutschland und Russland im europäischen Kontext - Möller, Horst; Cubar'jan, Aleksandr O. (Mitteilungen der Gemeinsamen Kommission für die Erforschung der jüngeren Geschichte der deutsch-russischen Beziehungen, 2023)
The seventh volume of Communications from the German & Russian Historical Committee documents colloquia held in 2013 in Moscow and 2014 in Berlin devoted to the theme, "The First World War: Germany and Russia in a European Context." In eighteen bilingual essays, renowned historians explore cross-national aspects of this "primal catastrophe of the 20th century."